Porous Hydrodynamic Journal Bearing Analysis Using Micropolar Fluid in Steady-State Condition - Ujjal Baidya (Japanese Society of Tribologists, 2019)
The objective of the present work is to study theoretically, the steady-state performance of finite hydrodynamic porous journal bearings under micropolar lubrication. The fluid pressure in porous matrix follows Darcy’s equation. In the film zone, the modified Reynolds equation is developed considering micropolar lubrication theory. Both Darcy’s and modified Reynolds equations are solved using finite difference technique with successive over-relaxation method to obtain the steady-state film pressure. The steady-state performance characteristics are evaluated in terms of non-dimensional load carrying ability, friction force and friction parameter of a finite journal bearing for different values of micropolarity viz, lm and N, and varying characteristics of porous bearing. The results show that the micropolar fluid is better than the Newtonian fluid when load carrying ability and friction parameters are concerned. The slip has a beneficial effect in terms of increase in load carrying ability and reduction in friction parameter approximately to 0.7, beyond which the advantage diminishes. lm exhibits an optimal value around 10.0. In case of industrial machinery and home appliances which uses the porous bearings and where the lubricant either gets contaminated with micro-elements or dust, mixing of additives will return better results.